Quantitative Spatial Analysis Of Cluster Patterns And Spatial Integration In The Celuk Creative District, Gianyar, Bali - Putri, Ni Putu Ratih Pradnyaswari Anasta; Wahyudi Linggasani, Made Anggita; Wicaksana, Gde Bagus Andhika (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
Celuk Village in Gianyar Regency, Bali, has evolved organically into a prominent silver craftsmanship corridor, forming a unique creative economy ecosystem where production workshops, commercial galleries, and tourist interaction spaces coexist within an interconnected spatial hierarchy. This study employs a spatial quantitative approach to analyse distribution patterns, spatial relationships, and functional hierarchies among 70 silver workshops and galleries across a defined 6-month research period. Spatial point data were collected through GPS-based field surveys, validated with positional accuracy tolerance ≤ 3 m, and processed using QGIS software to perform Point Pattern Analysis (PPA) and Kernel Density Estimation (KDE). The analysis identifies clustering tendencies and spatial density hierarchies, revealing a linear aggregation pattern concentrated along the primary west–east corridor connecting Gianyar and Denpasar. Statistical spatial correlation was measured using Nearest Neighbour Index (NNI = 0.69), indicating clustered distribution, supported by strong positive spatial autocorrelation (Moran’s I = +0.89, p < 0.05), confirming significant spatial dependence between neighbouring business units. To clarify the term functional mapping, field observations incorporated structured indicators of Building Function (production, exhibition, mixed use), Architectural Typology (traditional workshop, modern gallery, hybrid façade, adaptive building), and Activity Intensity Level (frequency of visible workers, visitor presence, façade permeability, sidewalk spill-out, and temporal peak markers). The findings demonstrate that spatial configuration in Celuk is shaped not only by economic efficiency and proximity, but also by symbolic cultural markers—such as temples and traditional ornaments—that reinforce spatial identity and distinguish the district from purely commercial corridors. While clustering supports collaborative resource sharing and visibility, the study also detects spatial imbalance between the main spine and peripheral lanes, signalling emerging commercial pressure and declining activity on secondary routes. For sustainable creative district growth, a scale-sensitive integrated spatial planning framework is recommended, applying thematic production–display–tourism zoning supported by community-based governance to maintain economic–cultural balance, walkability, and cultural authenticity. This research contributes empirical spatial metrics and a replicable methodological structure for developing culture-based creative districts in Bali and Indonesia.